Design of a compact dual-mode dual-band microstrip bandpass filter based on semi-fractal CSRR - Alqaisy M.A.; Ali J.K.; Chakrabarty C.K.; Hock G.C. (2023)
Various complementary split ring resonators (CSRRs) are used as defected ground structures (DGSs) in the bandpass filter (BPF) design for different communication applications. In this paper, a hybrid CSRR has been introduced as a DGS in the ground plane of a dual-mode microstrip BPF to produce a new compact filter with dual band response. The proposed CSRR structure is essentially based on the conventional square double ring one, but with the inner ring made in the form Minkowski-like pre-fractal curve. Simulation and performance evaluation of the proposed filter have been carried out using a method of moment based EM simulator; the IE3D. Simulation results show that the resulting filter offers a dual passband response. The higher passband is attributed to the dual mode microstrip ring structure, while the lower passband is as a result of the embedded CSRR DGS structure, which implies an extra filter miniaturization. Results also show that the position of the lower passband could be varied, to certain extent, without affecting the position of the higher passband. This can be performed by the application of higher fractal iteration level to the inner split ring and/or dimension scaling of the whole CSRR structure. This feature makes the proposed filter suitable as a candidate for use in a wide variety of communication systems incorporating dual band operation.